Benzimidazole tethered thioureas as a new entry to elastase inhibition and free radical scavenging: Synthesis, molecular docking, and enzyme inhibitory kinetics. (22nd June 2021) - Ujan, Rabail; Channar, Pervaiz Ali; Saeed, Aamer; Abbas, Qamar; Rafique, Hummera; Ashraf, Saba; Rind, Mahboob Ali; Hassan, Abbas; Ul‐Hamid, Anwar; Hassan, Mubashar; Raza, Hussain; Seo, Sung‐Yum
Abstract: The porcine pancreatic elastase inhibition and free‐radical scavenging play a crucial role in age progression. All the series of 10 newly synthesized benzimidazole thioureas (4a‐j ) were assessed for elastase inhibition and radical scavenging activity to identify the suitable anti‐aging ingredient for cosmetics products. The compounds 4e, 4f, 4g, and 4h showed inhibition better than the standard, while compound 4f showed the most significant elastase inhibition with the IC50 value of 1.318 ± 0.025 μM compared with oleanic acid IC50 13.451 ± 0.014 used ±1.989 and 41.563 ± 0.824, respectively, as standard. Molecular docking studies were performed and the compound 4f showed binding energy of 7.2 kcal/mol. Kinetics studies revealed inhibition of the pancreatic elastase in a competitive manner. The relative binding energy and structure activity relationship (SAR) identified compound 4f as an effective inhibitor of porcine pancreatic elastase. Compounds 4e and 4i showed remarkable free‐radical scavenging activity with SC50 values of 26.421. Abstract :